Chudley-McCullough Syndrome: A Recognizable Clinical Entity Characterized by Deafness and Typical Brain Malformations. (February 2021) - Blauen, Aglaë; Stutterd, Chloe A.; Stouffs, Katrien; Dumitriu, Dana; Deggouj, Naima; Lockhart, Paul J.; Leventer, Richard J.; Nassogne, Marie-Cécile; Jansen, Anna C.
Chudley-McCullough syndrome, a rare autosomal recessive disorder due to pathogenic variants in the GPSM2 (G-protein signaling modulator 2) gene, is characterized by early-onset sensorineural deafness and a typical combination of brain malformations, including ventriculomegaly, (partial) agenesis of the corpus callosum, cerebellar dysplasia, arachnoid cysts, frontal subcortical heterotopia, and midline polymicrogyria. When hearing loss is managed early, most patients have minor or no impairment of motor and cognitive development, despite the presence of brain malformations. We report 2 cases of Chudley-McCullough syndrome, one presenting with congenital deafness and normal development except for speech delay and one presenting prenatally with ventriculomegaly and an atypical postnatal course characterized by epileptic spasms, deafness, and moderate intellectual disability. These highlight the challenges faced by clinicians when predicting prognosis based on pre- or postnatal imaging of brain malformations. We have also reviewed the phenotype and genotype of previous published cases to better understand Chudley-McCullough syndrome.